(untitled) (Revista Española de Derecho Internacional, 2009)
This article analyses the meaning of the concept of yihad in the Islam. It concludes that the yihad as Holy War was the predominant concept in the traditional Islamic Law (fiqh). The article also studies that the above mentioned medieval concept is defended today by certain sectors of radical Islamism. Opposite to this position, there are other voices in the islamic world which proclaim peace and conciliation with other civilizations.